2015
DOI: 10.18388/abp.2015_1014
|View full text |Cite
|
Sign up to set email alerts
|

Interindividual variability of atorvastatin treatment influence on the MPO gene expression in patients after acute myocardial infarction.

Abstract: Myeloperoxidase (MPO) and C-reactive protein (CRP) may play critical roles in generation of oxidative stress and the development of the systemic inflammatory response. The aim of the study was to determine the effect of atorvastatin therapy on the MPO gene expression and its plasma level in relation to lipids level lowering and an anti-inflammatory response in patients after acute myocardial infarction. The research material was represented by 112 samples. Thirty-eight patients with first AMI receiving atorvas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…In AMI, long-term hypoxia and ischemia of myocardial cells leads to aerobic metabolic disorder due to coronary occlusion, and then causes hyperemia and edema of myocardial interstitial cells, and myocardial cell degeneration and necrosis, accompanied by a large amount of inflammatory cell infiltration (10). A large number of free radicals are generated in the tissues and the peroxide destruction of oxygen free radicals mainly damages the structure and function of myocardial cell membranes, damages the mitochondria, cuts off the cells energy supply and destroys lysosomes to cause cell autolysis (24). The myocardium of accelerated ischemia develops from reversible damage to irreversible degeneration and necrosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In AMI, long-term hypoxia and ischemia of myocardial cells leads to aerobic metabolic disorder due to coronary occlusion, and then causes hyperemia and edema of myocardial interstitial cells, and myocardial cell degeneration and necrosis, accompanied by a large amount of inflammatory cell infiltration (10). A large number of free radicals are generated in the tissues and the peroxide destruction of oxygen free radicals mainly damages the structure and function of myocardial cell membranes, damages the mitochondria, cuts off the cells energy supply and destroys lysosomes to cause cell autolysis (24). The myocardium of accelerated ischemia develops from reversible damage to irreversible degeneration and necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…The myocardium of accelerated ischemia develops from reversible damage to irreversible degeneration and necrosis. Malignant arrhythmia appears, thereby causing ventricular remodeling and cardiac dysfunction (24). Recanalization and reperfusion therapy is the most effective treatment now, but I/R can further damage the myocardium, for which the important mechanism is oxidative stress; the greater the duration of myocardial ischemia and hypoxia the greater the oxidative stress and myocardial damage, and the more severe the disease (25).…”
Section: Discussionmentioning
confidence: 99%
“…The 1,25(OH) 2 D/VDR signalling pathway has the capacity to mediate antibacterial, antiviral, and anti-inflammatory activity [ 29 ]. VDR polymorphism has been associated with increased risk of several diseases, with some of the genetic variants being less responsive than others to 1,25(OH) 2 D in suppressing inflammatory processes, thus favouring the development of cutaneous inflammatory conditions [ 41 ] and possibly of chronic periodontitis [ 5 , 42 ].…”
Section: Vitamin D and Vitamin D Receptor (Vdr)mentioning
confidence: 99%
“…In addition, it has been shown that VDR polymorphism, in the presence of exogenous aetiological factors (i.e., tobacco smoke and alcohol), is associated with increased risk of chronic periodontitis and other inflammatory conditions. Some genetic variants may be less responsive to 1,25(OH) 2 D in suppressing inflammation, thus favouring bacteria-induced tissue damage, while other variants are associated with low bone-mineral density, thus making alveolar bone vulnerable to bacterial plaque-induced inflammatory bone resorption [ 5 , 41 , 42 , 52 , 53 ].…”
Section: Oral Mucosal Immunitymentioning
confidence: 99%
“…Decreased cutaneous conversion of 7-dehydrocholesterol to cholecalciferol occurs with higher melanin content. 9 Accounting for skin pigmentation and sun behaviors are informative, yet understudied areas in the context of serum 25(OH)D and BC. Second, body mass index (BMI) has been used a surrogate marker of adiposity.…”
Section: Introductionmentioning
confidence: 99%